Yang aneh yang magis dua puluh cerpen pilihan - Ana Balqis; Jimadie Shah Othman; Khairil Idham Ismail; Lokman Hakim; Lutfi Ishak; Hafizah Iszahanid; Faisal Tehrani; Fahd Razy; Anwar Ridhwan (Penerbitan Kata-Pilar, 2017)
The twenty short stories selected in this manuscript are doors, each leading to its own strange and magical space. The unique stories such as clone humans with fangs and helicopter-dropped suns ,the woman with the bomb is also a witch who tricks the Professor, dragons come back to life, man who lost his tongue and many more.